Preparing, Not Repairing - Cannon, Leah; Dosch, Brianne; Gunderman, Hannah (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
LibGuides are widely used in academic libraries to organize information and resources to better serve their users, yet the maintenance of LibGuides across many different academic libraries ranges from neglectful to fastidious, making it difficult to determine the accuracy and helpfulness of information on LibGuides (Randtke & Burrell, 2012). A Scrapy-based Python script developed by the SIS Programming Team was used to crawl the LibGuides of each academic library member of the ARL, and a second script was used to test the HTTP status of each link.  Maintaining link validity in LibGuides is a proactive and strong first step toward patron satisfaction, and using a combination of scripts and manual processes can be a proactive way to monitor link validity and fight link rot.